Exploring students’ competence, autonomy and relatedness in the flipped classroom pedagogical model - Zainuddin, Zamzami; Perera, Corinne Jacqueline (Taylor & Francis, 2017)
This study aimed at identifying the differences between a flipped classroom and a non-flipped classroom instructional model, based on the Self-Determination Theory (SDT). This study employed a mixed-method research approach, using post-tests, questionnaires and focus group interviews during the data collection process. Sixty-one students were the respondents involved in a non-randomised experiment with a control group design, while 10 representative students participated in a focus-group discussion. The results reported that post-test 1 showed no significant difference between the two groups of flipped and non-flipped classroom instruction (t = 1.68, p =.474), while post-tests 2 and 3 were significantly different (t = 5.54, p =.007 <.05) and (t = 10.17, p =.001 <.05). This finding shows that students in the flipped learning environment were more competent handling online tasks and activities, and were able to control their learning outcomes. The survey results showed that the flip-class setting fostered better peer interaction and autonomous learning skills among the students. The flip-class environment had also a positive influence on students’ intrinsic motivation. The qualitative findings from the students’ interviews revealed that students were motivated by the video-recorded lectures, self-regulated learning environments, engagement in class activities and peer interaction. Conclusions from this study showed that the flip-class setting had successfully established the basic psychological needs of SDT, namely: competency, autonomy and relatedness in a flipped classroom model.